ANALISIS PERILAKU PENGUSAHA TRAVEL UMRAH DAN KBIHU DALAM BERTRANSAKSI PAKET UMRAH MENURUT PERSPEKTIF ETIKA BISNIS ISLAM: Studi Kasus Di Travel Umrah Dan KBIHU Kabupaten Tasikmalaya - Cecep Sudrajat; Hasan Basri; Salsabila Sevenia3 (ARMUZNA : Jurnal Manajemen Haji dan Umrah (MHU), 2024)
This research was undermined by the existence of a consumer who purchased his basic needs using a scale, then the scale he used was still using the old version of the scales. After the purchase of the basic needs, the consumer said he suffered from a lack of weight, so that consumer did not accept consumer rights fully. The principle of Islamic business ethics is one of the benchmarks in the world of trade, because to know the behavior of traders in transactions can be measured from the principles of the Islamic ethics of business: unity, honesty, justice, accountability, and freedom of will. Without the application of Islamic business ethics, traders' behaviour in transactions is not consistent with Islamic Shariah. The purpose of this research is to know the concepts of trading, the practices of trading used, as well as to know and not the principles of Islamic business ethics. To obtain this research, the author uses data collection techniques such as interviews, observations, and documentation. This research approach uses a qualitative approach with case study research methods. For data analysis, data reduction, presentation, and sample is used. The results of this research showed that the concept of trading in transactions in the Beautiful Dawn Shop is able to perform well, provide good service to the buyer, and for transaction traders use the tool proof of the manual transaction using written receipts. In transacting according to the ethical perspective of Islamic business traders have done well the principles of fairness, free will, responsibility, virginity and goodness. However, there is still something that traders do not conform to the principles of Islamic business ethics, which is the principle of balance, because traders still like to do fraud in the measurement or weighing of 15 grams to 159 grams.